Mental demands and thriving of older workers: The role of work ability - Sousa, I. C.; Baltazar, D. (Revista de Administração de Empresas, 2024)
The aging of the working population and the increasing mental demands at work represent a challenge to the sustainability of working life and the organizations’ competitiveness. Research has focused on thriving at work as a proxy for career sustainability, particularly in its final phase. However, there is limited knowledge about the mechanisms underlying the relationship between thriving and its antecedents. This study aims to examine the mediating role of work ability in the relationship between mental demands at work and thriving among older workers. A sample of 163 workers responded to an online questionnaire. Results support the mediation hypothesis, but the direct effect of mental demands on thriving was insignificant, emphasizing the importance of work ability. Theoretical and practical implications are discussed.